New bioleaching: the metallurgical option - Alpaca Arena, Melitón (1998)
Ironically mention that the newest way to get pure metals is carried out with the help of the oldest organisms on the planet . Indeed the most commonly used in the leaching bacteria are actually bacteria tonnage , ie the oldest and most primitive forms of life and that as a modern classification of Biology , form a domain thereof . In the mid- 70 advances in gene sequencing discovered the microbial diversity of the world and as a result the old classifications have been replaced by a tree of three domains : Tonnage bacteria , Bacteria and Eukarya . The branch of Eukarya organisms made ​​up of cells with nucleus, is where animal life, plant and algae and fungi fit . The second branch form Bacteria , and although most are lethal to man many of them have proven to be the ideal companion of man in his struggle to decontaminate the environment. Finally there is the branch of tonnage bacteria, which in the opinion of many scientists are the first forms of life that originated in marine abyssal fissures and hot springs, from the presence of light. The most commonly used bacterial leaching bacteria are Thiobacillus . The presence of Thiobacillus ferroxidans in drainage water from coal mines and their correlation with the dissolution of minerals , recently became apparent in 1957 . The presence of microorganisms in such a hostile environment , and the existence of soluble metal and sulfuric acid, caused shock at the time and even skepticism.